Spatial inequities in COVID-19 vaccination in Philadelphia by race and income - Angela D'Adamo; Alina Schnake-Mahl; Usama Bilal; Jane Miller (Preventive Medicine Reports)
Objective: Vaccination is a key intervention to prevent severe COVID-19, but in the early months of vaccination availability in the United States, there were wide spatial inequities in vaccination by neighborood racial-ethnic composition and socioeconomic status. To explore whether and how these inequities persisted, we examined the association between neighborhood-level income and racial-ethnic composition and COVID-19 vaccination coverage in Philadelphia, and described trends in inequities in 2021 and 2022. Methods: Using vaccination data for 46 Philadelphia neighborhoods (zip codes), from the Philadelphia Department of Public Health, we estimated vaccination coverage on April 18th, September 26th, and November 21st of 2021, as well as April 3rd, June 26th, and August 7th of 2022. We estimated and compared average vaccination coverage by neighborhood-level income and racial-ethnic composition. We explored inequities in coverage by estimating absolute and relative differences in vaccination by date. Results: COVID-19 vaccination coverage varied substantially by neighborhood-level income and racial-ethnic composition. On all dates, rates were higher in high income and non-Hispanic White neighborhoods compared to medium-income, low-income, mixed, and non-Hispanic Black neighborhoods. The absolute and relative differences in vaccination between neighborhoods narrowed over time but persisted through August 2022. Conclusions: This study provides evidence for the importance of policies that target low-income and non-Hispanic Black neighborhoods during pandemics, including during vaccination rollout, as they have experienced a disproportionate infection, hospitalization, and mortality burden due to COVID-19 and experienced lower vaccination rates.